Microscopic modelling of international (re-)hospitalisation effects in the CEPHOS-LINK setting. (16th July 2019) - Zauner, Günther; Urach, Christoph; Bicher, Martin; Popper, Niki; Endel, Florian
Re-hospitalisation rates have become popular as a quality indicator among healthcare researchers, and politicians for cost containment and quality improvement. Within the EU-FP7 project CEPHOS-LINK an agent-based model (ABM) is integrated for Austria, Slovenia, and Veneto region of Italy for answering questions regarding long time planning effects for psychiatric (re)-hospitalisation under special constraints using national routine databases combined by data pooling processes. The simulation framework is based on a modular concept with the core module GEPOC (generic population concept), developed within the DEXHELPP consortia project in Austria, parameterised for regional forecast. Demographic changes, their simulated effects on (re)-hospitalisation, changes in distance to service and the effect of changes in the diabetes mellitus prevalence are calculated as forecast for Austria, Slovenia, and Veneto region. Results are gathered on a personal level, depicted and described on age/gender groups. Furthermore the (re)-hospitalisations in each country are mapped to costs, based on purchasing power parity.